Pembuatan Jaringan Sosial Peneliti Berbasis Facebook Yang Memanfaatkan Situs Sitasi Artikel Ilmiah Di Pusat Penelitian Universitas Kristen Petra - Ervina Utami Limpo; Adi Wibowo; Resmana Lim (Jurnal Infra, 2014)
Scientific journal is one of a media for researcher to publish their research result as a report. Pusat Penelitian (Puslit) is a framework in Petra Christian University Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) with objective to help and develop applied research activity for lecturer and or student. In 2012, Puslit develops a site for citation of scientific paper, as GudangPaper to accommodate research information/scientific research formation in Indonesia in form of article and or e-journal. In the following developing, GudangPaper want to be integrated with many social site to form a social network for the researcher, one of them is to create an application based on Facebook API. Based on the background problem, an application using Facebook API is designed with JavaScript SDK and PHP SDK from Facebook along with Facebook social plugin. Stages of application system design process are do a survey from 5 different e-journal repository sites that have social network system, analize database from GudangPaper, design the Data Flow Diagram and Entity Relationship Diagram for the application to be made. To make the user interface appealing, CSS framework, Bootstrap 2.0 is used. The results of this research are library management system, social feature such as groups and plugin from Facebook and connect the application with Facebook user as a promotion media and form the social network.